PENGARUH BRAND EQUITY TERHADAP REPURCHASE INTENTION MELALUI BRAND PREFERENCE PADA STARBUCKS COFFEE DI KOTA SEMARANG - Krisna Nur Huda; Sri Suryoko (Universitas Diponegoro, 2018)
The phenomenon of the rapid growth of coffee shops has evolved into a lifestyle in community. Starbucks Coffee is a coffee shop from the United States whose outlets always grow from year to year. However, a faster growth of outlets is not followed by declining the brand survey results of the Starbucks Coffee in 2015-2017. Starbucks sales in Indonesia also tend to fluctuate is no exception in Semarang City.This study aims to determine the influence of Brand Equity on Repurchase Intention through Brand Preference as an intervening variable. The result of the research shows that Brand Equity has positive and significant correlation to Repurchase Intention with number of regretion 0.202, while Brand Preference has positive and significant correlation to Repurchase Intention with number of regretion 0.306. Brand Preference variable in this research is able to mediate Brand Equity relationship to Repurchase Intention with p-value 0.000. The conclusion of this study proves that with the existence of Brand Preference, then repurchase intention will appear. Furthermore, in order to create Brand Preference, the strength of Starbucks Coffee Brand Equity in Semarang City needs to be improved which then will bring up the Repurchase Intention. Suggestions that can be given to increase repurchase intention in Starbucks Coffee at Semarang City should conduct price adjustment evaluation and add form of promotion for customers.